Knowledge acquisition and product development capability magnify competitive advantage : insight into higher education institutions of Pakistan - Akram, Kashif; ul Haq, Muhammad Abrar; Raza, Saqlain; Fazal, Hina; Suhardi, Mulyadi (Penerbit Universiti Kebangsaan Malaysia, 2022)
With the emergence of a knowledge-based economy, knowledge has become an integral factor in providing a competitive advantage for organizations including higher education institutions. The objective of this study is to empirically examine the mediating effect of product development capability (PDC) in the relationship between knowledge acquisition (KA) and competitive advantage (CA) in public higher education institutions (PHEIs) of Pakistan. Data were collected through a self-administered questionnaire. A total of one hundred questionnaires were distributed through random sampling technique to vice-chancellors of PHEIs eliciting eighty-six respondents or a response rate of eighty-six percent. Data were analysed by using PLS through a structural equation modelling approach. The findings revealed significant positive effect of KA and PDC on CA. Additionally, KA also produced a significant positive effect on PDA. Further, PDA was shown to mediate the relationship between KA and CA. The current research provides more specific direction on how practitioners can strategically gain CA through KA and PDC within context of PHEIs of Pakistan.